Analysis of Changes in Rural and Urban Land and Building Tax Rates in DKI Jakarta in 2024 from the Perspective of the Principle of Equity - Ar Raiyan, Azka Tsaqif; Neobing, Chealsee; Gunawan, Khalisha Naila; Augustin, Sherine Ollivia (CV. Publikasi Indonesia, 2025)
The changes in the Rural and Urban Land and Building Tax (PBB-P2) rates in DKI Jakarta for 2024 raise questions about their fairness and alignment with the principles of equity, especially considering the significant socio-economic disparities within the region. This study aims to analyze the impact of the 2024 PBB-P2 rate changes in DKI Jakarta, focusing on their compliance with the principles of equity in taxation, and to assess how these changes affect different social groups. The research approach uses a descriptive qualitative method with secondary data analysis of the latest regulations and data related to PBB-P2 rates. The results show that these tariff changes attempt to reflect the principles of vertical and horizontal equity, although there are challenges in their implementation, such as the gap between the value of the tax object and the taxpayer's ability to pay. This study provides policy recommendations to optimize the principle of equity in the application of PBB-P2 tariffs, so as to increase public confidence in the tax system in DKI Jakarta.